Sustainability of the Northern Ireland Nephrops Fishing Fleet : An analysis of the Balance between Fishing Capacity and Fishing Opportunities.: An analysis of the Balance between Fishing Capacity and Fishing Opportunities. (2016) - Samuel, Aurelia; Burgess, Diane, 1973-; Lundy, Mathieu
No abstract available